Pengaruh Literasi Keuangan Dan Inklusi Keuangan Terhadap Pengelolaan Keuangan UMKM Di Kecamatan Kisaran Barat Kabupaten Asahan - Munthay, Salik Farhan; Sembiring, Masta (Politeknik Ganesha Medan, 2024)
Financial Literacy is a person's understanding or ability to measure financial concepts and have the ability to manage finances well. Financial literacy is very important for MSMEs in managing their business finances. Financial inclusion is the availability of access to various institutions, products and financial services according to the needs and capabilities of the community in order to improve people's welfare. This study aims to examine and analyze the effect of financial literacy and financial inclusion on MSME financial management in Kisaran Barat District. This type of research is quantitative research. The total population in this study was 390 MSME actors and the sample in this study were 80 MSME actors in Kisaran Barat District. Data collection techniques in this study were interviews and questionnaires. The data analysis method uses multiple linear regression analysis. The research results show that financial literacy and financial inclusion partially and simultaneously influence financial management.